REVIEW ON PHARMACOVIGILANCE STUDY OF TELMISARTAN IN HYPERTENSION PATEINTS - SUHAS, DABHADE; DEEPAK, BHOSLE; KAVITA, ATRE (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Hypertension is a chronic condition in which blood pressure is higher than normal range. For treatment of hypertension, a broad range of antihypertensive medication is currently available, choice is depend upon where cheaper ones would be equally effective, may have negative impacts on national healthcare budgets.Â  Antihypertensive drugs are frequentlyÂ  associated with adverse drug reactions (ADRs) that may limit treatment options and reduce patient adherence, which may hinder blood pressure control. These drugs are believed to cause ADRs or symptoms that make patients feel worse than they did before beginning drug therapy for their "asymptomatic" disease. The science and systems used for systematically identifying and correlating drugs and side-effects and taking corrective actions fall under the discipline of Pharmacovigilance. Key words: Hypertension, Pharmacovigilance, Adverese Drug Reactions, Telmisartan.